Pertumbuhan dan Hasil Kubis Bunga akibat Pemberian Pupuk Organik Cair Nasa dan Zat Pengatur Tumbuh Hormonik - Erida Nurahmi; Hasinah HAR; Sri Mulyani (Fakultas Pertanian, Universitas Syiah Kuala, 2010)
Growth and Yield of Cauliflower Caused by NASA Liquid Organic Fertilizer and Plant Growth Regulator HormonesABSTRACT. Cauliflower plants in great demand, so the development of aquaculture should be developed to obtain the desired quality and quantity. The purpose of this study is to determine the concentration of NASA's Liquid Organic fertilizers and plant growth regulator Hormonik proper growth and yield of cauliflower. This research was conducted at the experimental station of Faculty of Agriculture University of Syiah Kuala Darussalam Banda Aceh, Seed Varieties used were obtained from the CV Hoggar. Aria Enterprises Banda Aceh, the foliar fertilizer used was NASA Liquid Organic fertilizers and plant growth regulator produced Hormonik PT. Natural Nusantara Indonesia. The soil used in soil types Entisol top soil from the Experimental Farm Faculty of Agriculture, University of Syiah Kuala, Darussalam Banda Aceh. There are two factors that investigated the concentration of NASA's Liquid Organic fertilizers are composed of three levels: 2, 4 and 6 cc l-1 water, and plant growth regulators Hormonik which consists of three levels: 1, 2 and 3 cc l-1 water. Variable which observed were plant height, leaf number, stem diameter at the age of 21, 35 and 49 days after planting, and the wet weight berangkasan, flower weight were observed at harvest 60 days after planted. Result of study showed that the combination of concentration and NASA Liquid Organic fertilizers Hormonik growth regulator that shows growth and better results were found at a concentration of 4 cc l-1 water of liquid organic fertilizer Nasa and 2 cc / l water of growth regulators hormonik.